Hypercoagulation in colorectal cancer: What can platelet indices tell us?. (5th September 2014) - Seretis, Charalampos; Youssef, Haney; Chapman, Mark
Abstract: Colorectal cancer, as all solid malignancies, is accompanied by changes in the haemostatic mechanism favoring the establishment of a thrombotic potential, with platelets playing a key-role in this framework; they further link colorectal cancer progression and hypercoagulation with the immune-response against the neoplastic spread. Under this rationale, various studies have assessed the use of platelet indices as prognostic markers of the biological behavior of colorectal cancer, demonstrating significant results. We herein attempt to summarize in a narrative and critical approach the relevant available data and the underlying pathophysiology, stressing the necessity of a more thorough understanding and future implementation of platelet indices in all stages of care we deliver to colorectal cancer patients.